2002
DOI: 10.1046/j.1365-2605.2002.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of seminal osmolarity in the regulation of human sperm motility

Abstract: Mammalian sperm at ejaculation are suspended in the seminal plasma, a heterogeneous mixture deriving from the testicular/epididymal fluid and from secretions of seminal vesicles, prostate and bulbourethral glands. Biochemical characteristics of seminal fluid change along the male reproductive tract when considering its inorganic and organic composition and pH but it is known that in each region of the male genital tract seminal osmolarity is higher than that of serum. It has been previously demonstrated that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 17 publications
4
37
1
1
Order By: Relevance
“…Such a view is supported by the fact that is a major trait showing variability (Sato et al 2007, Hernández-Ló pez et al 2008, providing females (or their reproductive tracts) a substrate for male quality assessment. Since different glands contribute to its formation, a small variation in the amounts of constituents contributed by each gland yields structurally diverse seminal coagula, where changes in its components, independently from sperm concentration, severely impair fertility (Rossato et al 2002, Mikhailichenko & Esipov 2005, Khosrowbeygi & Zarghami 2007, de Lamiranda 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a view is supported by the fact that is a major trait showing variability (Sato et al 2007, Hernández-Ló pez et al 2008, providing females (or their reproductive tracts) a substrate for male quality assessment. Since different glands contribute to its formation, a small variation in the amounts of constituents contributed by each gland yields structurally diverse seminal coagula, where changes in its components, independently from sperm concentration, severely impair fertility (Rossato et al 2002, Mikhailichenko & Esipov 2005, Khosrowbeygi & Zarghami 2007, de Lamiranda 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The seminal coagulum also provides a viscous matrix preventing sperm diffusion out of the ejaculate, and in many primate species contains semenogelins as well as prostate-specific antigen and prostatic acid phosphatase, the enzymes needed to induce ejaculate clotting and its further liquefaction respectively (Lilja 1993, Dorus et al 2004, Clark & Swanson 2005. In addition, semenogelins induce sperm quiescence to avoid spending energy during migration throughout the male tract (Robert & Gagnon 1996, Cooper 1998, Rossato et al 2002, de Lamiranda 2007. Furthermore, prostaglandins found in the seminal coagulum induce contractions of the smooth musculature of the female tract to enhance sperm transport (Prins 1998, Suarez & Pacey 2006.…”
Section: Introductionmentioning
confidence: 99%
“…No differences are seen in sodium or potassium concentrations between ejaculatory fractions (Kareskoski et al 2005). The addition of potassium to semen extenders improves motility of stallion (Padilla and Foote 1991) and human sperm (Karow et al 1992), but Rossato et al (2002) found no correlation between the ionic composition and the osmolarity of human seminal plasma. Intracellular concentrations of potassium are higher than those of seminal plasma, and therefore potassium levels are linked to sperm concentration.…”
Section: Sodium Chloride and Potassiummentioning
confidence: 91%
“…Cryopreserved sperm underwent the standard freeze-thaw procedure using enhanced sperm freeze solution (Conception Technology). Sperm in semen or in vitro reagents were handled in such a way that physiological osmolarity was not compromised [13][14][15]. SDTS was assessed by observing the sample under a phase contrast microscope at 400X magnification.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between SDTS and HOS is that both are tail swellings, but it is considered SDTS when swelling is unexpectedly exhibited in fluids holding physiological osmolarities, while HOS occurs if sperm are exposed to hypo-osmotic conditions [1,13]. Physiological osmolarity in this context refers to the osmolarity values of body fluid like semen, and in vitro developed reagents in which human cells, including spermatozoa, maintain their cellular integrity and perform normal physiological functions [13][14][15]. Our study investigated the prevalence of SDTS in sperm samples that are commonly encountered in an andrology laboratory, and secondly the influence of SDTS in HOS-test results.…”
Section: Introductionmentioning
confidence: 99%